Subclinical hypothyroidism in eastern Nepal: A hospital based study - Rohil, V; Mishra, AK; Shrewastwa, MK; Mehta, KD; Lamsal, M; Baral, N; Majhi, S (Kathmandu University Medical Journal, 2010)
Background: Subclinical hypothyroidism itself is associated with serious complications and also there is a known risk of subclinical hypothyroidism patients getting converted into overt disease. Objectives: The objective of the present study was to find out the prevalence of subclinical hypothyroidism in the suspected cases i.e. amongst the cases attending the thyroid laboratory at B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Materials and methods: It was a retrospective cross sectional study. Data of the free T3, free T4 and TSH estimations of the year 2007 of the Thyroid lab at BPKIHS, Dharan, Nepal was analyzed. ELISA based free T3, free T4 and TSH tests in the serum had been performed in all the cases. Results: Total cases were 1714 including 24.446% males and 75.554% females. Cases with raised TSH levels were 26.021%, cases with normal TSH levels were 54.66% and cases with low TSH levels were 19.316%. Total 350 cases (20.42 %) had subclinical hypothyroid dysfunction which includes 84 (4.901 %) males and 266 (15.519%) females. And the maximum percentage of cases in either gender was between the age groups 20 -59 years. Conclusion: The prevalence of subclinical thyroid hypothyroidism amongst the suspected cases was 20.42% which is much higher compared to the other parts of the world. The highest percentage was found in the female age group 20 - 59 years. The routine screening of the whole population is not cost effective and on the basis of the present study it is suggested that there may be routine screening of the selected populations, especially women between 20 to 59 years of age in Nepal region. The preferred screening method advised is a sensitive ELISA based TSH test. Key words: Subclinical hypothyroidism DOI: 10.3126/kumj.v8i2.3565 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 231-237